The Effect Of Quality Of Work Life And Motivation On Employee Performance Of Pt. Bank Rakyat Indonesia (Persero) Barru Branch - Fajrin, Fajrin; Muhammad Yusuf; Andi Nur Fitrianti (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a type of quantitative research with the aim of determining the influence of the quality of work life and motivation on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Barru Branch. The type of data used in this study is quantitative data obtained from questionnaires that are shared and related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26 application regarding the influence of quality of work life and motivation on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Barru Branch which has been discussed in the previous chapter, the author draws an important conclusion that the quality of work life has a positive and significant effect on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Barru Branch while motivation has a positive and significant effect on the performance of employees of PT. Bank Rakyat Indonesia (Persero) Barru Branch.